Online Costumer Review and Influencer Marketing Impact toward Purchase Decision at Cicada Resort Bali Ubud, Autograph Collection - I Gusti Agung Gede Witarsana; I Wayan Dena Aril Varilino; Cahyo Purnomo Loanata; Ni Desak Made Santi Diwyarthi (Westscience Press, 2026)
Improving purchase decisions in the hospitality sector is very important, so it is necessary to know the factors that affect it, several factors that can affect purchase decisions in this digital era include online customer reviews and influencer marketing, therefore this study aims to find out the influence of online customer reviews and influencer marketing for purchase decisions at the Cicada Resort Bali Ubud hotel, Autograph Collection, which is located in Gianyar Regency, Bali. This study uses a quantitative approach involving 90 respondents with an age range of >21 years - 50 years who come from Indonesia and outside Indonesia and are guests who have stayed at Cicada Resort Bali Ubud, Autograph Collection which was selected using purposive sampling techniques and analyzed by multiple linear regression data analysis techniques processed using the SPSS application version 27. From this study, it was found that online customer reviews and influencer marketing have a positive and significant influence on purchase decisions at Cicada Resort Bali Ubud, Autograph Collection with online customer reviews and influencer marketing contributed 65.6% simultaneously to purchase decisions, and partially Online customer reviews have a contribution of 50.44% and influencer marketing of 15.16%, which confirms the importance of online customer reviews and influencer marketing in improving purchase decisions at Cicada Resort Bali Ubud, Autograph Collection.